KUAT GESER TANAH LEMPUNG DENGAN VARIASI PENAMBAHAN LIMBAH BETON - fitridawati soehardi; Marta Dinata; Yoan De Nanda Herru; Junaidi (LPPM Universitas Abdurrab, 2025)
Clay soil tends to expand when wet and contract when dry, which can cause cracks in the soil or damage to the building structure above it if not handled properly. One effort that can be carried out is chemical stabilization using both conventional stabilization materials and the use of alternative stabilization materials, both organic and inorganic. The aim of this research is to increase the shear strength of the soil by adding varying percentages of 5%, 10%, 15% and 20% of concrete waste. The method used is an experimental method in the laboratory using SNI 3420:2016 testing for shear strength. The research results show that there is an increase in cohesion values ​​and shear angles along with the addition of concrete waste. The highest increase was found in the percentage of 20% addition of concrete waste to the original soil, namely the cohesion value was 0.400 kg/cm2 and the shear angle value was 24.567 0.